Estimasi Dampak Penyalahgunaan Narkoba pada Produktivitas Kerja: Studi Corss Sectional Pada Pekerja di Indonesia - Sudaryo, Mondastri Korib; Antasari, Erma (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Prevalence of drugs abuse among workers is still high. Drug use among workers has a negative impact on the health and safety of both workers and the community. This study was aimed to examine the relationship between impaired work productivity and drug behaviour among workers in Indonesia.Methods: This study used secondary data from the national survey on drug abuse among workers in 2017.  The total sample size was 34,397 persons. We used cox regression model to estimates the Prevalence Ratios (PR) and its 95% confidence intervals for associations between drug abuse and impaired work productivityResults: Drug abuse, marijuana and methamphetamine, used by workers were associated with impaired work productivity. Drug abuse in workers increased the likelihood of impaired work productivity by 2.3 times (p-value: <0.001; 95% CI: 1.97-2.73). Meanwhile, the use of marijuana types increased the probability of impaired work productivity by 1.6 times (p-value <0.001; 95% CI: 1.32-2.00). Workers using methamphetamine drugs were 1.29 times more likely to experience impaired work productivity than workers who did not use methamphetamine (p-value: 0.03; 95% CI: 1.03-1.62).Conclusion: impaired work productivity among workers was significantly associated with drug abuse